2020
DOI: 10.2196/preprints.21578
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Clinical Decision Support System for the Treatment of COVID-19 with Multi-Criteria Decision-Making Techniques (Preprint)

Abstract: BACKGROUND The outbreak of coronavirus disease 2019 (COVID-19) was first reported in December 2019. Until now, many drugs and methods have been used in the treatment of the disease. However, no effective treatment option has been found and only case-based successes have been achieved so far. OBJECTIVE This study aims to evaluate the COVID-19 treatment options using multi-criteria decision-makin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Nardo et al [19] showed the application of multi-criteria decision analysis to determine weights for eleven criteria in order to prioritize COVID-19 non-critical patients for admission to hospital in healthcare settings with limited resources. Yildirim et al [20] evaluated the available COVID-19 treatment options in hospitals. For the evaluation, they used a hybrid methodology based on the application of two well-known multi-criteria tools: (1) Preference Ranking Organization Method for Enrichment of Evaluations (PROMETHEE) and (2) Vlsehriterijumska Optimizacija I Kompromisno Resenje (VIKOR) method.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Nardo et al [19] showed the application of multi-criteria decision analysis to determine weights for eleven criteria in order to prioritize COVID-19 non-critical patients for admission to hospital in healthcare settings with limited resources. Yildirim et al [20] evaluated the available COVID-19 treatment options in hospitals. For the evaluation, they used a hybrid methodology based on the application of two well-known multi-criteria tools: (1) Preference Ranking Organization Method for Enrichment of Evaluations (PROMETHEE) and (2) Vlsehriterijumska Optimizacija I Kompromisno Resenje (VIKOR) method.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In general, there are only a few articles in the literature that consider the application of hybrid multi-criteria techniques for the evaluation of hospital capacities in crisis situations [14,15,21]. Despite the fact that decision making under the conditions of the COVID-19 pandemic and crisis situations in general is accompanied by a greater or lesser number of uncertainties, there are only a few studies that apply fuzzy numbers to treat uncertainties [20]. Additionally, the analysis of the literature shows that there is no study that considers the possibility of including spa centers in healthcare systems in order to reduce the pressure on primary hospital capacities under the conditions of COVID-19 pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%